Analisis Pelaksanaan Praktikum Biologi SMA Negeri 1 dan SMA Negeri 2 Kecamtan Tambusai - -, Muliadong (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2016)
The aim of research is to know the implementation practical biology of high school in Tambusai district. The type of this research is descriftive research. The population of this research is all of students class XI IPAhigh school 1 Tambusai and students class XI IPA high school 2 Tambusai. The research used âpurposive samplingâ is some population to take the sample. The date used was likert scale technique. The analysis result showed high school 1 that frecuency practical implementation with average percentage 81,83%, the student interest in practical with average percentage 88,36%, the time of practical implementation with average percentage 82,00%, preparation and practical implementation with average percentage 88,70%. The analysis result showed high school 2 that frecuency practical implementation with average percentage 65,49%, the student interest in practical with average percentage 75,22%, the time of practical implementation with average percentage 73,00%, preparation and practical implementation with average percentage 86,25%.